An Examination of Violence Practiced against Disabled Brazilians in Relation to Sustainable Development - Kirakosyan, Lyusyena (Disability Studies Quarterly, 2014)
Although there are no national data and statistics regarding violence against disabled citizens in Brazil, findings from a number of small-scale research studies suggest that it is a problem of considerable magnitude. This article draws on the existing literature on violence and oppression, empirical studies on violence against disabled people in Brazil and interviews with a sample of disabled Brazilians to argue that the most prevalent forms of violence in the nation are subtle and concealed forms of oppression that reproduce discriminatory power structures in Brazilian society. Such power structures prevent the developing world in general and Brazil in particular from securing democratic and sustainable development in the post-2015 era, when disadvantaged people must be at the center. The analysis is organized in three parts. First, I outline briefly the main issues in defining impairment, disability and violence, since these represent political choices that shape policy decisions. Second, I analyze the forms of violence that affect disabled Brazilians and the relationships and institutions that create and sustain them. Third, I describe and evaluate the government's key current strategies aimed at addressing violence against disabled Brazilians. The purpose here is to suggest ways in which violence against disabled Brazilians can be addressed in public policies as a sustainable development issue and thus help close the "gap" between disabled and nondisabled populations to create truly sustainable democratic societies that honor human dignity.